2021
DOI: 10.1002/rmb2.12423
|View full text |Cite
|
Sign up to set email alerts
|

Higher fibrotic content of endometriotic lesions is associated with diminished prostaglandin E2 signaling

Abstract: Purpose While the prevailing view holds that the prostaglandin E2 (PGE 2 ) signaling plays a vital role in endometriosis, PGE 2 also is known to be anti‐fibrotic. We investigated the immunostaining of COX‐2, EP2, and EP4, along with fibrotic content in ovarian endometrioma (OE) and deep endometriosis (DE) lesions, and in OE lesions from adolescent and adult patients. In addition, we evaluated the effect of substrate stiffness on the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 96 publications
(279 reference statements)
4
24
0
Order By: Relevance
“…Indeed, endometrial stromal cells cultured on a stiff matrix display reduced expression of COX‐2, EP2, and EP4 with or without TGF‐β1 stimulation. 28 Furthermore, the combined use of a recently established mouse model of adenomyosis 25 and a mouse model of simulated menstruation 49 lends further support for this proposal (Mao et al, in preparation).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, endometrial stromal cells cultured on a stiff matrix display reduced expression of COX‐2, EP2, and EP4 with or without TGF‐β1 stimulation. 28 Furthermore, the combined use of a recently established mouse model of adenomyosis 25 and a mouse model of simulated menstruation 49 lends further support for this proposal (Mao et al, in preparation).…”
Section: Discussionmentioning
confidence: 88%
“… 27 Indeed, we recently reported that, in the context of endometriosis, the expression of COX‐2 and E‐series receptor type 2 (EP2) and EP4 is reduced as endometriotic lesions became more fibrotic. 28 , 29 In addition, endometriotic stromal cells cultured in stiffer matrices demonstrate decreasing expression of COX‐2, EP2, and EP4, 28 suggesting reduced PGE 2 signaling as the extracellular matrix (ECM) becomes stiffer. As ectopic endometrium, both adenomyosis and endometriotic lesions share the same and defining hallmark of cyclic bleeding, 30 they also share similar, but not exactly identical molecular processes that underpin lesional progression owing to different microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, on average the OE lesions in adolescents would be more likely to be cystic and less fibrotic than those in adults, which would mean that these patients would be more likely to respond to non‐steroid anti‐inflammatory drugs (NSAIDs) therapy since the PGE2 signaling is less likely to be attenuated. 97 They may also respond to therapies that target the EP2 and/or EP4 receptors. 139 In contrast, OE lesions in adults may not respond well to either NSAID treatment 97 or therapies that target the EP2 and/or EP4 receptors, 139 especially when the lesions are highly fibrotic.…”
Section: Discussionmentioning
confidence: 99%
“… 97 They may also respond to therapies that target the EP2 and/or EP4 receptors. 139 In contrast, OE lesions in adults may not respond well to either NSAID treatment 97 or therapies that target the EP2 and/or EP4 receptors, 139 especially when the lesions are highly fibrotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation